CLASS DISTINCTION AS REPRESENTED BY TWIN PLANETS IN "UPSIDE DOWN" MOVIE - Kartini, Eva; Natsir, M.; Ariani, Setya (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2021)
The purposes of this research were to find the class distinction in character of Adam and Lagavulin and the alienation in character of Adam from the Upside Down movie. This research utilized the method of qualitative research with the technique of observing and used content analysis. The data sources of this research were the script and movie of Upside Down. The data were taken from the dialog of each character and some narrations of Adam indicating the characteristics of class distinction and types of alienation based on the theory of Karl Marx. From the findings of this research, the characters in the movie revealed there were 7 characteristics of class distinction by looking at two types of class, bourgeoisie and proletariat, those are brutal exploiter, the ruler, own the means of production, productive force, the oppressed class, have no means of production, the revolutionary. Also, from the character of Adam, he revealed there were 4 types of alienation with the types as follow, the alienation of the worker in his product, the alienation from the act of production, the alienation from the true essence of our species-being, the alienation of a worker from other workers.